(untitled) (Bangladesh Pharmaceutical Journal, 2019)
Diarrhoea is a public health problem in developing countries. It is therefore important to identify plants with antidiarrhoeal activity. Melochia corchorifolia and Glochidion thomsonii have been used in folk medicine to alleviate several diseases. The present study was performed to investigate the anti-diarrheal properties of ethanolic extract of M. corchorifolia whole plant and G. thomsonii bark. Anti-diarrheal potential was evaluated using castor oil and MgSO4 induced diarrhea, GI motility test as well as castor oil induced enteropooling assay in mice. Extracts were used at 250 and 500 mg/kg per orally. Loperamide (10 mg/kg p.o) was used as standard drug. The ethanolic crude extracts exhibited statistically significant and dose-dependent (250 and 500 mg/kg) anti-diarrheal effect against the total number of episodes of defecation as well as diarrheal feces. In animals pretreated with MC and GT extract showed 42.53% (p<0.05) and 53.13% (p<0.001) protection at a dose of 250 mg/kg and 89.40% (p<0.001)and 57.47% (p<0.001) protection at 500 mg/kg against castor oil induced diarrhea. The MC extract at 500 mg/kg exhibited significant (p<0.05) inhibition of diarrhea (51.04%) in MgSO4 induced diarrhea. In BaSO4 induced GI motility test both the extracts inhibited GI motility and GT at 500 mg/kg dose 38.77% which was highly significant (p<0.01). In the Castor oil induced enteropooling assay MC 250 and 500 mg/kg and GT 250 and 500 mg/kg reduced the intestinal fluid accumulation by 27.42% and 48.39% (p<0.01) and 38.71% (p<0.05) and 51.61% (p<0.01), respectively. The results suggested that both the extracts possessed significant antidiarrhoeal properties which was comparable with standard drug, loperamide and further studies are required to evaluate these effects and the potential of the plant. Bangladesh Pharmaceutical Journal 22(2): 192-199, 2019